Seed dormancy, germination, emergence and seed longevity in Galinsoga parviflora and G. quadriradiata. (31st October 2013) - De, B; Devos, R; Claerhout, S; Bulcke, R; Reheul, D; Andersson, Lars
Summary Galinsoga quadriradiata (hairy galinsoga) and Galinsoga parviflora (smallflower galinsoga, gallant soldier) are very troublesome weeds in many vegetable row crops in Europe. To optimise management strategies for Galinsoga spp. control, an in‐depth study of germination biology was performed. Germination experiments were conducted to evaluate the impact of light and alternating temperatures on germination of a large set of Galinsoga populations. Seedling emergence was investigated by burying seeds at different depths in a sandy and sandy loam soil. Dormancy of fresh seeds harvested in autumn was evaluated by studying germination response in light at 25/20°C with and without nitrate addition. Seed longevity was investigated in an accelerated ageing experiment by exposing seeds to 45°C and 100% relative humidity. Galinsoga spp. seeds required light for germination; light dependency varied among populations. Seedling emergence decreased drastically with increasing burial depth. Maximum depth of emergence varied between 4 and 10 mm depending on soil type and population. In a sandy soil, emergence percentages were higher and seedlings were able to emerge from greater depths than in a sandy loam soil. Freshly produced G. parviflora seeds, harvested in autumn, showed a varying but high degree of primary dormancy and were less persistent than G. quadriradiata seeds that lack primary dormancy. Lack of primary dormancy of freshly harvested G. quadriradiata seeds and light dependency for germination may be used to optimise and develop Galinsoga management strategies.